Enfranchising Foreigners: What Drives Natives' Willingness to Share Power? - Anna Maria Koukal; Reiner Eichenberger; Patricia Schafera (Center for Research in Economics, Management and the Arts (CREMA), 2019)
Universal suffrage is a core element for the functioning of democracy. However, with growing international mobility, an increasing share of the resident population has no suffrage. This paper analyzes the conditions under which domestic citizens are willing to extend suffrage to foreign residents. We explore a new municipality level dataset of 35 Swiss referenda on the enfranchisement of foreigners at the cantonal level. The Swiss setting provides a unique laboratory for capturing the drivers of the enfranchisement of foreigners, as it allows for measuring the actual native electorate's revealed preferences. We find evidence that perceived cultural and economic threats hinder the enfranchisement of foreigners.
Keywords: D72; J15; P16; 330; foreigners' voting rights; political integration; threat hypothesis; democratization